DINAMIKA PERKEMBANGAN KOMUNITAS DAYAK HINDU BUDHA BUMI SEGANDU DI INDRAMAYU - Nuhrison M Nuh (Harmoni, 2012)
The focus of the discussion of this research is the development of Dayak Hindu Budha Bumi Segandu followers’ community, government policy and social relations between this community and the surrounding society. This study used a qualitative approach in the form of case study on a local community, which has its own teaching and identity. This community was established by Takmad, initiated with establishing the martial-arts (silat) residence and ilmu ngaji rasa. The concept of teaching is not based on the holy book, any religious sect, religion or cultural roots, but to take the attitude model and behavior of Semar and Pendawa Lima characters.